Smoking and fracture risk: a meta-analysis. - Kanis, J; Johnell, O; Oden, A; Johansson, H; De Laet, C; Eisman, J; Fujiwara, S; Kroger, H; McCloskey, E; Mellstrom, D; Melton, L; Pols, H; et al. (2005)
Smoking is widely considered a risk factor for future fracture. The aim of this study was to quantify this risk on an international basis and to explore the relationship of this risk with age, sex and bone mineral density (BMD). We studied 59,232 men and women (74% female) from ten prospective cohorts comprising EVOS/EPOS, DOES, CaMos, Rochester, Sheffield, Rotterdam, Kuopio, Hiroshima and two cohorts from Gothenburg. Cohorts were followed for a total of 250,000 person-years. The effect of current or past smoking, on the risk of any fracture, any osteoporotic fracture and hip fracture alone was examined using a Poisson model for each sex from each cohort. Covariates examined were age, sex and BMD. The results of the different studies were merged using the weighted beta-coefficients. Current smoking was associated with a significantly increased risk of any fracture compared to non-smokers (RR=1.25; 95% Confidence Interval (CI)=1.15-1.36). Risk ratio (RR) was adjusted marginally downward when account was taken of BMD, but it remained significantly increased (RR=1.13). For an osteoporotic fracture, the risk was marginally higher (RR=1.29; 95% CI=1.13-1.28). The highest risk was observed for hip fracture (RR=1.84; 95% CI=1.52-2.22), but this was also somewhat lower after adjustment for BMD (RR=1.60; 95% CI=1.27-2.02). Risk ratios were significantly higher in men than in women for all fractures and for osteoporotic fractures, but not for hip fracture. Low BMD accounted for only 23% of the smoking-related risk of hip fracture. Adjustment for body mass index had a small downward effect on risk for all fracture outcomes. For osteoporotic fracture, the risk ratio increased with age, but decreased with age for hip fracture. A smoking history was associated with a significantly increased risk of fracture compared with individuals with no smoking history, but the risk ratios were lower than for current smoking. We conclude that a history of smoking results in fracture risk that is substantially greater than that explained by measurement of BMD. Its validation on an international basis permits the use of this risk factor in case finding strategies.